2014
DOI: 10.1007/s40368-014-0136-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of active and passive distraction during restorative treatment in children using an iPad versus audiovisual eyeglasses: a randomised controlled trial

Abstract: Active distraction using an iPad demonstrated better performance than passive distraction using AV glasses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
49
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 18 publications
7
49
0
1
Order By: Relevance
“…Characteristics of the included studies are shown in Table . Among these nine studies published between the years 2010 and 2017, five studies are crossover design and four studies are randomized controlled design . In total, 697 children received dental treatments ranging from 3‐ to 16‐year‐old.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Characteristics of the included studies are shown in Table . Among these nine studies published between the years 2010 and 2017, five studies are crossover design and four studies are randomized controlled design . In total, 697 children received dental treatments ranging from 3‐ to 16‐year‐old.…”
Section: Resultsmentioning
confidence: 99%
“…Al‐Khotani's clinical trial also showed a statistically significant difference in using audiovisual distractor . On account of Attar's crossover clinical trial evaluated pre‐operate anxiety, so we excluded this study in this depart …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…playing a video game) in reducing patient anxiety as proven by the results of this study [22][23]. Previously several paediatric hospitals have tried to utilize the iPad technology and MP3 players with soft padded headphones to support a child through painful medical procedures.…”
Section: Discussionmentioning
confidence: 76%
“…Previously several paediatric hospitals have tried to utilize the iPad technology and MP3 players with soft padded headphones to support a child through painful medical procedures. They have indicated that there will be further opportunities to use tablet computers as distraction tools when caring for children [23].…”
Section: Discussionmentioning
confidence: 99%